Is the use of ozonated oil effective in the treatment of oral lesions? : systematic review of clinical studies = ¿Es el uso del aceite ozonizado efectivo en el tratamiento de las lesiones orales? : una revisión sistemática de estudios clínicos - Yabar Condori, Jusef
The aim of this study was to perform a systematic review (SR) of the therapeutic effect of ozonated oil for oral lesions treatment. A SR was conducted according to the PRISMA guidelines. The Medline (PubMed), Embase, Cochrane Library, Scielo and LILACS were investigated, together with manual searches, to extract all publications until December 2020, including randomized and non-randomized clinical trials reporting the effects of ozonated oils on the management of oral lesions when compared with other methods. The risk of bias (RoB) of the studies included were assessed by using the RoB 2 tool and ROBINS-I. After analyzing the titles and reading the abstracts, 1932 articles were excluded; the remaining 25 passed a full-text evaluation. Ultimately, 13 articles were included in this SR. There was heterogeneity of the results regarding healing times and intervals of ozonated oil application for the treatment of each type of oral lesion, but in general, there was a shorter healing time when ozonated oil was used as therapy, and no adverse effects were reported. Despite the limited information found and the lack of rigorous methodological standards for the use of ozonated oil on oral lesions, a positive effect was suggested. The findings indicated an advantage in terms of shorter healing times when compared with other conventional treatments. No adverse effects were reported, showing safety and reliability for patient's treatment.